Two Early Medieval Swords from the Masovian-Prussian Borderland - Jarosław Ościłowski (Fasciculi Archaeologiae Historicae, 2017)
The paper discusses two early medieval swords from the region of Zawkrze in Masovia. The first one was found in the cemetery in Dąbek near Mława and the other one was discovered near Żuromin at the River Wkra. Their blades belong to Type X according to Ewart Oakeshott’s classification. Both swords underwent X-ray and metallographic examinations in the Laboratory of Bio- and Archaeometry of the Institute of Archaeology and Ethnology of the Polish Academy of Sciences in Warsaw.